Exploration of food materials and components showing the suppressing effect on absorption of strontium and the promoting effect on excretion of cesium in vivo. Issue 6 (2016) - Uehara, Yuya; Ishizuka, Kana; Shimamura, Yuko; Yasuda, Michiko; Shimoi, Kayoko; Masuda, Shuichi
No abstract available